Cruel Optimism: Zika, Lex Sportiva, and Bodies of (Alleged) Contagion - De Lisio, Amanda; Fusco, Caroline (Columbia Journal of Gender and Law, 2020)
Previous literature has noted the connection between sport and corporate environmentalism, especially that which has positioned the sport mega-event as a facilitator of “sustainable” development. David Chernushenko (1994) was the first environmentalist to propose a model of ecologically sustainable development for sport and recreation management, which was criticized for the notable appeal to neoliberalcapitalist advancement. Due to eco-driven protests in Denver (1974), Toronto (1989), and Rome (1997), the International Olympic Committee (IOC) amended the Olympic Charter to reflect growing environmental concern. Yet the IOC model has—much like the work of Chernushenko—continued to favor finance. Recent literature has documented the extent to which the Olympic pillar of “sustainability,” intended to “integrate sustainable development into their policies and activities,” has allowed for deceptive corporate marketing to merely greenwash the Games. It is from this context that the Aedes aegypti or Yellow Fever mosquito rapidly emerged—now host to Dengue, Chikungunya, Zika, Mayaro, and other viruses. We borrow from Lauren Berlant the notion of “cruel optimism” to describe structural/institutional ideologies (e.g., allegiance to the monogamous, heteronormative family) that facilitate capitalist expansion, even in the midst of (environmental) crisis.3 While the literal destruction of the cityscape (whether sport-prompted or not) has cemented an economic logic into the physical landscape and modern mind, we contend that scientific-technological communities need to (more carefully) protect and privilege the pre-existent “nature-made” strategies of sustainability. So, to make an authentic commitment to the environment, the IOC—as emblematic of an international conglomerate repeatedly encouraged to rewrite and recreate sovereign law—would need to legally enforce the protection of local ecologies as it has legally enforced the protection of corporate sponsorship and the Olympic brand.